THE ROLE OF YOUTH IN COMBATING SOCIAL INEQUALITY: EMPOWERING THE NEXT GENERATION - Purna Laxmi Jamatia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Social inequality is a pressing issue in India that disproportionately affects young individuals. This analysis explores the impact of social inequality on various domains, including education, employment, housing, health, and social inclusion. It highlights the challenges faced by young people in accessing quality education, securing stable employment, finding affordable housing, maintaining good health, and participating fully in society. However, youth-led organizations and activists have emerged as powerful agents of change in addressing these disparities. Youth-led interventions have focused on bridging the educational gap, promoting equal job opportunities, advocating for affordable housing, improving healthcare access, and championing social justice causes. These initiatives have demonstrated effectiveness in raising awareness, influencing policies, creating support networks, and mobilizing communities. However, challenges such as limited resources and contextual nuances must be considered when transferring successful models to different contexts. The long-term impact of youth empowerment in combating social inequality is significant. Youth involvement fosters leadership skills, active citizenship, and community engagement, creating a ripple effect of social change. Successful models developed in India can serve as valuable examples for other communities, emphasizing the universal nature of social inequality and the collaborative efforts required to address it. Sustained support for youth-led initiatives, recognition of their contributions, and the creation of inclusive environments are crucial for building a more equitable and just society. By harnessing the potential of youth, India can effectively combat social inequality and empower its young population to shape a brighter future for all.